Cognitive resilience following paediatric stroke: Biological and environmental predictors. (March 2020) - Anderson, Vicki; Darling, Simone; Mackay, Mark; Monagle, Paul; Greenham, Mardee; Cooper, Anna; Hunt, Rod W.; Hearps, Stephen; Gordon, Anne L.
Abstract: Little is known about resilience after paediatric stroke (PS), or the factors that contribute to better outcomes. Rather, research emphasis has been on impairment, measured through cross-sectional or retrospective designs, often heavily weighted to children presenting for clinical or rehabilitation follow-up. Implementing a resilience framework, this study aimed to investigate cognitive recovery post-stroke and factors that contribute to cognitive resilience at 12 months following PS. In a single site, prospective, longitudinal study (baseline, 1, 6, 12 months post-stroke), 61 children (55.7% male) aged 0–18 years, with a diagnosis of acute arterial ischemic stroke were recruited. Neurological status, lesion and child characteristics were collected at diagnosis. Cognitive, language and motor skills were assessed directly using age-appropriate, standardised tools. Parents rated their mental health, and child social and adaptive abilities. Participants were classified as 'resilient' (74%) or 'vulnerable' based on 12-month cognitive scores. The resilient group demonstrated more intact acute neurological status and higher language and adaptive abilities 1-month post-stroke; 88% of the vulnerable group had strokes involving both cortical and subcortical regions. Neonatal stroke, large lesions, cortical-only lesions, and middle cerebral artery involvement were associated with poorer cognition over the 12 months post-stroke. Absence of seizures and older age at stroke predicted better cognitive outcomes. In summary, most children surviving PS are cognitively resilient at 12 months post-insult. Risk and protective factors identified may guide targeted clinical intervention for more vulnerable children. Future research is needed to explore cognitive resilience trajectories beyond 12 months post-stroke. Highlights: Most PS survivors show intact cognition at 12 months, suggesting resilience after such brain insult is unexpectedly common. Risk and protective factors identified in the present study may provide a guide for targeting clinical follow-up and intervention. Future research is needed to explore cognitive resilience trajectories beyond 12 months post-stroke.